An integrated ultrasonic-assisted enzymes as a single extraction unit for gallic acid from labisia pumila (kacip fatimah) - Noor Adilah, Md Salehan (2018)
Labisia pumila (locally known as Kacip fatimah) extract contains phenolic compounds such as gallic acid that have multiple biological effects. Ultrasound-assisted extraction (UAE) is widely reported for the extraction of medicinal plants and herbs due to its economical and green technology. Therefore, this study applied UAE with unified enzymatic extraction (EnE) to enhance the extraction yield of gallic acid from Labisia pumila. The influence of five parameters on the extraction of gallic acid from Labisia pumila were investigated: extraction time (1–8 h), sample-to-solvent ratio (1:6, 1:8, 1:10, and 1:12 wt/wt), temperature (40, 50, 60, and 80 °C), sonication (10%, 20%, and 40% duty cycle), and cellulase concentration (0.025, 0.05, 0.1, 0.2, and 0.3 g/L). The power intensity of 8.66 W/cm2 was implemented using an ultrasonic processor Q700 (700 watts, 20 kHz). The results showed that the gallic acid yield was the highest at 50 °C with 1:10 sample-to-solvent ratio for aqueous extraction (AE) with 1.0251 ± 0.0569 mg/g of gallic acid extracted. Whereas, both ultrasound-assisted extraction (UAE) and enzymatic extraction (EnE) techniques gave the highest yield at 40% duty cycle and 0.05 g/L cellulase concentration with 1.8425 ± 0.1191 mg/g and 1.28565 ± 0.1760 mg/g gallic acid extracted, respectively. The result of the ultrasound-assisted enzymatic extraction (UEnE) indicated an increased trend when the extraction time was increased from 1 to 7 h. However, beyond 7 h the yield declined indicating that the degradation of gallic acid may have initiated. The highest gallic acid amount obtained from UAEnE was 2.9287 ± 0.4060 mg/g after 7 h of extraction with 2.91-fold increment compared with the AE result. Thus, the integrated single unit ultrasonic-assisted enzyme extraction successfully improved the gallic acid extraction from Labisia pumila.